2022
DOI: 10.1111/jfbc.14512
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa presents cytotoxicity against melanoma cancer cell lines (A‐375 e B16‐F10) and improves chemotherapy activity by increasing oxidative stress

Abstract: Melanoma frequently presents a poor chemotherapy response. In this scenario, investigations for new therapies are essential. Thus, cocoa is highlighted in this area since it presents many biological properties. This study investigated the anticarcinogenic activity of cocoa in melanoma cell lines (A‐375 and B16‐F10). Melanoma and fibroblast (HFF‐1) cell lines were exposed to different concentrations of cocoa seeds (30 to 2000 ug/ml) at 24 and 72 h. Cocoa was also associated with paclitaxel IC50. We conducted vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In in vitro studies, the fibroblast or lymphoblast cell line are most often used as a reference line for normal body cells, which is why we decided to use the NHDF line, like some other authors [ 46 , 47 , 48 , 49 , 50 , 51 ], in combination with the mentioned cancer lines. Other fibroblast lines can also be used as normal cell lines [ 52 , 53 , 54 ]. In addition, the reference compounds free terpyridine and PTA, as well as copper(I) precursor [Cu(MeCN) 4 ][PF 6 ], were also tested.…”
Section: Resultsmentioning
confidence: 99%
“…In in vitro studies, the fibroblast or lymphoblast cell line are most often used as a reference line for normal body cells, which is why we decided to use the NHDF line, like some other authors [ 46 , 47 , 48 , 49 , 50 , 51 ], in combination with the mentioned cancer lines. Other fibroblast lines can also be used as normal cell lines [ 52 , 53 , 54 ]. In addition, the reference compounds free terpyridine and PTA, as well as copper(I) precursor [Cu(MeCN) 4 ][PF 6 ], were also tested.…”
Section: Resultsmentioning
confidence: 99%
“…133 The research found that cocoa can decrease the cell viability and cell growth of melanoma cell lines, i.e., B16-F10 and A-375, by inducing oxidative stress in cells. 134 7.5.7. Myricetin.…”
Section: Therapeutic Strategies For the Treatmentmentioning
confidence: 99%
“…Cocoa is a traditional medicine that can be used in the treatment of malaria, worm expellers, and wound healing . The research found that cocoa can decrease the cell viability and cell growth of melanoma cell lines, i.e., B16-F10 and A-375, by inducing oxidative stress in cells …”
Section: Therapeutic Strategies For the Treatment Of Skin Cancermentioning
confidence: 99%
“…Cell viability was determined by MTT assay (Sigma-Aldrich; Merck KGaA). The cells were seeded into 96well plates (1x10 4 cells/ml) for 24 h. After a preliminary literature review (Loo et al 2005; (Mello et al 2022) and pre-experiment results, A2780/A2780T cells were treated with paclitaxel at a concentration gradient of 20,15,10, 5, 2.5 µg/ml. After 48 h, 50 µL MTT (Sigma-Aldrich; Merck KGaA) was added to each well and incubated for additional 4 h. Finally, dimethyl-sulfoxide (150 µl) was added to each well, and the absorbance of the cells at 570 nm was measured using a microplate reader (SpectraMax, Molecular Devices).…”
Section: Mtt Assaymentioning
confidence: 99%